Increasing Alcohol Taxes: Analysis of Case Studies From Illinois, Maryland, and Massachusetts - Ramirez, Rebecca L. (J Stud Alcohol Drugs, 2017)
OBJECTIVE: The effectiveness of alcohol taxes in reducing excessive alcohol consumption and related problems is well established in research, yet increases in U.S. state alcohol taxes are uncommon. This study examined how alcohol tax increases occurred recently in three U.S. states, what public health’s role was, and what can be learned from those experiences. METHOD: Review of available documentation and news media content analysis provided context and, along with snowball sampling, helped identify proponents, opponents, and neutral parties in each state. Thirty-five semi-structured key informant interviews (lasting approximately 1 hour) were conducted, transcribed, and analyzed for common themes. RESULTS: State routes to alcohol tax increases varied, as did the role of public health research. Use of polling data, leveraging existing political champions, coalition building, drawing on past experience with legislative initiatives, deciding revenue allocation strategically, and generating media coverage were universal elements of these initiatives. Tax changes occurred when key policy makers sought new revenue sources or when proponents were able to build coalitions broader than the substance abuse field. CONCLUSIONS: Translation of scientific evidence on the effectiveness of increasing alcohol taxes into public health interventions may occur if legislative leaders seek new revenue sources or if broad-based coalitions can generate support and sustained media coverage. Policy makers are generally unaware of the health impact of alcohol taxes, although public health research may play a valuable role in framing and informing discussions of state alcohol tax increases as a strategy for reducing excessive alcohol use and alcohol-related harms.